1995
DOI: 10.1126/science.7863329
|View full text |Cite
|
Sign up to set email alerts
|

p53-Independent Expression of p21 Cip1 in Muscle and Other Terminally Differentiating Cells

Abstract: Terminal differentiation is coupled to withdrawal from the cell cycle. The cyclin-dependent kinase inhibitor (CKI) p21Cip1 is transcriptionally regulated by p53 and can induce growth arrest. CKIs are therefore potential mediators of developmental control of cell proliferation. The expression pattern of mouse p21 correlated with terminal differentiation of multiple cell lineages including skeletal muscle, cartilage, skin, and nasal epithelium in a p53-independent manner. Although the muscle-specific transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

50
613
2
3

Year Published

1996
1996
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 982 publications
(668 citation statements)
references
References 48 publications
50
613
2
3
Order By: Relevance
“…Deletion of p21 was not able to substitute for p53 de®ciency in the rescue of the MDM2 null embryonic lethality, described above (Montes de Oca Luna et al, 1997). Moreover, although the p21 CIP1 gene is transcriptionally activated by p53 (el-Deiry et al, 1993), p21 CIP1 is also upregulated during myogenic di erentiation by a p53-independent mechanism thought to involve MyoDmediated transactivation (Parker et al, 1995;Guo et al, 1995;Halevy et al, 1995;Missero et al, 1995). It has also been shown that p21 CIP1 is poorly expressed in RMS cells lines, concomitant with both MyoD and p53 inactivity, and failure to G 1 arrest (Otten et al, 1997).…”
Section: Digging Deeper ± Prb and P53 At The Crossroadsmentioning
confidence: 99%
“…Deletion of p21 was not able to substitute for p53 de®ciency in the rescue of the MDM2 null embryonic lethality, described above (Montes de Oca Luna et al, 1997). Moreover, although the p21 CIP1 gene is transcriptionally activated by p53 (el-Deiry et al, 1993), p21 CIP1 is also upregulated during myogenic di erentiation by a p53-independent mechanism thought to involve MyoDmediated transactivation (Parker et al, 1995;Guo et al, 1995;Halevy et al, 1995;Missero et al, 1995). It has also been shown that p21 CIP1 is poorly expressed in RMS cells lines, concomitant with both MyoD and p53 inactivity, and failure to G 1 arrest (Otten et al, 1997).…”
Section: Digging Deeper ± Prb and P53 At The Crossroadsmentioning
confidence: 99%
“…The archetypal member of this family, p21, was isolated as a Cdk2-associated protein and an inhibitor of Cdk2 (Gu et al, 1993;Harper et al, 1993;Xiong et al, 1993a), a gene induced by the tumor suppressor p53 (El-Deiry et al, 1993) and a gene whose RNA expression is increased in senescent cells (Noda et al, 1994). In addition to being induced by p53, p21 is also induced by p53-independent pathways (Guo et al, 1995;Halevy et al, 1995;Jiang et al, 1994;Macleod et al, 1995;Michieli et al, 1994;Missero et al, 1995;Parker et al, 1995;Sheikh et al, 1994;Steinman et al, 1994;Zhang et al, 1995). In contrast to the p16 INK4A family, p21 can bind and inhibit a wider spectrum of CDKs .…”
Section: Introductionmentioning
confidence: 99%
“…Although the cyclin-dependent kinase inhibitor p21WAFl/Cipl has been proposed as the mediator of p53-induced cell cycle arrest after DNA damage, it has been shown that several stimuli now appear to induce its expression, independent of p53 function. The up-regulation of p21 has also been implicated during normal tissue development and differentiation (Macleod et al, 1995;Missero et al, 1995;Parker et al, 1995).…”
mentioning
confidence: 99%